The biomarkers of sarcopenia in elderly people - Kishiko Ogawa (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Sarcopenia is a very prevalent age-related decline in skeletal muscle mass and muscle strength, and it has a biologic basis and is a distinct clinical syndrome in elderly people that is associated with high risk for adverse health outcomes. Currently, many parameters can potentially be used to track age-related skeletal muscle decline; among these parameters, biochemical markers for sarcopenia may be particularly useful for developing different aspects of therapeutic intervention. Evidence indicates that extracellular heat shock protein 72 in plasma may be defined, as a potential biomarker of sarcopenia. Extracellular adenosine triphosphate in plasma may trigger the release of heat shock protein 72 during a bout of exercise. Muscle hypertrophy in elderly women was caused by 12-week resistance exercise training, and this hypertrophy induced a reduction in extracellular heat shock protein 72 and pro-inflammatory cytokines and insulin like growth factor-I. The phenomenon in circulating levels of biomarkers may result from the lack of understanding of the mechanisms in exercise or muscle anabolic and catabolic systems, or secreted cell stress proteins are part of an extracellular homeostatic signaling system. Using two or more biomarkers in combination to clearly identify one condition may be one of multiple solutions. Using biomarkers combinatorially may allow clinicians to identify different domains of the sarcopenia syndrome and give them useful insights about the pathophysiological process underlying the phenomenon.